2022
DOI: 10.3389/fpubh.2022.993534
|View full text |Cite
|
Sign up to set email alerts
|

Impact of public health education on the health status of the older migrant population

Abstract: BackgroundDue to an increasing aging population, China has experienced a rapid expansion in its internal older migrant population who face greater health risks and who have a relatively high demand for health education. Public health education is an important means of preventing diseases and promoting health. However, many studies have focused on the utilization, with few studies examining the impact of public health education on the health of the older migrant population in China.ObjectivesThis study analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Incorporating existing research, theories of social determinants of health (SDOH) and data availability, this study selects individual factors, socio-economic factors, health care factors, and migration factors as explanatory variables (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)35). Shown in Table 1, individual factors include age, gender, education level, and marital status (with or without a spouse); socio-economic factors include household registration type, housing expenditure (divided into high, medium, and low groups, with the low-expenditure group as the reference group), and family monthly income (divided into three types: low income group of 694$ and below, medium income group of 695-2083$, and high income group of 2084$ and above, with the low income group as the reference group).…”
Section: Methods Variables and Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporating existing research, theories of social determinants of health (SDOH) and data availability, this study selects individual factors, socio-economic factors, health care factors, and migration factors as explanatory variables (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)35). Shown in Table 1, individual factors include age, gender, education level, and marital status (with or without a spouse); socio-economic factors include household registration type, housing expenditure (divided into high, medium, and low groups, with the low-expenditure group as the reference group), and family monthly income (divided into three types: low income group of 694$ and below, medium income group of 695-2083$, and high income group of 2084$ and above, with the low income group as the reference group).…”
Section: Methods Variables and Data Sourcesmentioning
confidence: 99%
“…A representative view is that health communication significantly promotes the improvement of the health status of migrant older adults through mechanisms such as medical service accessibility, medical service utilization, and health literacy (19). Public health education can also improve the self-assessed health level of migrant older adults, and its impact on the health of rural migrant older adults in the eastern region with high age and high cultural level is greater (20)(21)(22). Participating in health check-ups and seeking medical attention for minor illnesses has a positive effect on the health status of migrant older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the existing research results ( 20 , 29 , 35 , 36 ) and data availability, this study includes mediator variables such as health behavior and social support. Health behavior includes public health behavior and healthcare-seeking behavior.…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that compared with those who did not receive public health education, receiving public health education resulted in a 4.1% improvement in self-health, and a reduction in the incidence of daily symptoms and diseases by 5.3 and 6.1% respectively, compared to those who did not receive public health education ( 17 ). Yan et al’s findings also showed that receiving public health education increased the probability of self-assessed health improvement by 5.4–6.1% among the older adult mobile population ( 20 ). Thirdly, the path of action of public health education in influencing the health of the mobile population.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation